Thermo-economic analysis of an innovative multi-generation system based on ammonia synthesis - Farhang, Behzad; Ghaebi, Hadi; Gollo, Somayeh Naseri; Javani, Nader (PERGAMON-ELSEVIER SCIENCE LTD, 2024)
In this study, an innovative cogeneration system is developed and investigated which aim is to produce electrical power, ammonia, and hydrogen. A Kalina cycle is designed for electricity supply. An ammonia synthesis reactor and an electrolyzer are utilized for production of ammonia and hydrogen. The projected system is examined from economic and technical viewpoints. The analysis reveals that the ammonia production rate growth has been primarily influenced by the hydrogen to nitrogen molar ratio and pressure of reaction. For the system, the efficiencies of energy and exergy as well as the products' total unit cost achieve 50.47 %, 51.41 % as well as 638.3 $/GJ, each. The outcomes underscore that the rate of the destructed exergy is 89.797 MW for the system. Furthermore, 6.528 kg/s of ammonia and 6.438 kg/h of hydrogen are achievable. From a purely economic point of view, the comprehensive sensitivity examination deduces that 3 factors, namely the reaction pressure, hydrogen to nitrogen molar rate, and input hydrogen molar rate, do exercise a positive impact on the products' total unit cost lessening. Lastly, results of thermodynamic sensitivity evaluation confirm that the offered system technical inefficiencies are correlated to the reaction temperature changes.
Keywords: Cogeneration plant; Thermodynamic analysis; Exergoeconomic analysis; Hydrogen production; Exergy efficiency; Ammonia; HYDROGEN-PRODUCTION; COGENERATION SYSTEM; MULTIOBJECTIVE OPTIMIZATION; MULTICRITERIA OPTIMIZATION; ENERGY; EXERGY; POWER; SOLAR; BIOMASS; WASTE; Science & Technology - Other Topics; Energy & Fuels